Terapia cognitiva conductual y la personalidad antisocial en los adolescentes, en la Parroquia 24 de Mayo, cantón Quevedo - Charcopa Vera, Leida Marisol (2019)
The personality of the human being is given by several elements, which as the passage of time passes, accentuating the formation of personality. The child from his early years is acquiring elements that incorporate their behavior, the first part is related to their parents, they are responsible for setting the example and the appropriate characteristics, which are adjusted to social and religious standards. The second part is related to the school, family context; the interaction between his friends and colleagues, affirm in his first years of life the personality with which he worked all his life, but this personality of the child can take another direction as his parents, friends and the context change their way of proceeding . Currently the sector of May 24 suffers from a serious problem, because adolescents have developed an antisocial personality disorder, due to false communication, lack of dialogue, inappropriate use of social networks, consumption of culture foreign, the lack of economic resources, the little affection given by his family, the consumption of substances and especially the lack of self-love. All these factors make adolescents use inappropriate practices that undermine their own personality. Faced with this problem, we have taken the decision to assume a leading role, and with the help of Quevedeña society try to solve this problem, providing psychological resources and improve the lives of these adolescents, conducting therapy campaigns to facilitate the lives of these young people as well as their parents